Effects of Open Versus Closed Skill Exercise on Cognitive Function: A Systematic Review - Gu, Qian; Zou, Liye; Loprinzi, Paul D.; Quan, Minghui; Huang, Tao (Frontiers in Psychology, 2019)
Background: Exercise modes can be divided into open skill exercise (OSE) and closed skill exercise (CSE). While research has shown that these two exercise modes may have different effects on cognitive function, this possibility has not been systematically reviewed. Objective: The purpose of the present review was to objectively evaluate the research literature regarding the effects of OSE versus CSE on cognitive function. Methods: Six electronic databases (Web of Science, EMBASE, Google Scholar, PubMed, PsycINFO, and SPORTDiscus) were searched from inception dates to December 2018 for studies examining the associations of OSE and CSE with cognitive function. The literature searches were conducted using the combinations of two groups of relevant search items related to exercise modes (i.e. OSE and CSE) and cognitive function. Articles were limited to human studies in all age groups. Both interventional and observational studies with full text published in English-language peer-reviewed journals were considered eligible. The search process, study selection, data extraction, and study quality assessment were carried out independently by two researchers. Results: A total of 1,573 articles were identified. Fourteen observational and five interventional studies met the inclusion criteria. Twelve of the 14 observational studies found both OSE and CSE to benefit cognitive function, and seven of these 14 observational studies supported superior effects of OSE compared with CSE for enhancing cognitive function. Three of the five interventional studies found that OSE (versus CSE) led to greater improvements in cognitive function in both children and older adults. Conclusion: Although the majority of studies in this review were observational cross-sectional designs, the review tends to support OSE as more effective for improving some aspects of cognitive function compared with CSE. More rigorous randomized control trials with long-term follow-ups are needed in order to confirm these differential cognitive effects of the two exercise modes.